Análise comparativa da evapotranspiração de referência estimada por diferentes métodos no município de limoeiro do norte, Ceará - Lima Junior, Francisco Eduardo Barros de (2008)
This work was aimed at selecting the best methods to estimate the reference evapotranspiration in comparison with the equation of Penman-Monteith-FAO. The methods of evapotranspiration estimation compared were: Jensen-Haise, Ivanov, Linacre, Hargreaves-Samani and Makkink. The analyzed data came from the automatic weather station belonging to the Unidade de Ensino e Pesquisa (Teaching and Research Unit) of the Instituto Federal de Educação, Ciência e Tecnologia do Ceará - Campus Limoeiro do Norte, Ceará, comprising the period (in 2007) from January 1st to December. The analysis was based on daily data, monthly data and by ten-day interval data using regression analysis and evaluating the Hoppinks (2002) correlation coefficient, the Willmott (et al., 1985) indexes and the Sentelhas and Campbell (1997) performance index . The results demonstrated that the method of Ivanov gave the best performance in the daily schedule, that in the ten-day schedule the methods of Ivanov and Hargreaves-Samani showed the best performance, and that in the monthly schedule, the methods of Linacre, Hargreaves-Samani and Ivanov showed the best performance. Despite the good performance of the Ivanov method with all three time schedules, we would advise the use of the Hargreaves-Samani method, in ten-day and monthly schedules, due to its greater ease of data collection and practicality in the calculation of reference evapotranspiration.